Tropes, Parables, and Performatives - Miller, J. Hillis (Joseph Hillis), 1928-2021 (Book collections on Project MUSE., 1991)
Tropes, Parables, Performatives collects J. Hillis Miller's essays on seven major twentieth-century authors: Lawrence, Kafka, Stevens, Williams, Woolf, Hardy, and Conrad. For all their evident differences, these essays from early to late explore a single intuition about literature, which may be framed by three words: "trope," "parable," and "performative."Throughout these essays Miller is fascinated with the tropological dimension of literary language, with the way figures of speech turn aside the telling of a story or the presentation of a literary theme. The exploration of this turning leads